Buried Probe in Complex Congenital Nasolacrimal Duct Obstructions: Clinical Profiles and Outcomes. Issue 4 (July 2015) - Gupta, Adit; Kamal, Saurabh; Javed Ali, Mohammad; Naik, Milind N
Abstract : Purpose: To report the clinical profiles and outcomes of buried probe variant of complex congenital nasolacrimal duct obstruction (CNLDO). Methods: Retrospective chart review of all patients endoscopically diagnosed as a buried probe variant of complex CNLDO, over a 3.5 year period from a single surgeon's (MJA) database were included in the study. A detailed lacrimal system evaluation was performed and intraoperative findings including nasal endoscopy were documented. A minimum follow up of 3 months following the final intervention was considered for analysis. Anatomical and functional success of the interventions was assessed at the final follow up. Results: Twenty-two eyes of 21 patients with buried probes were studied. The mean age at presentations was 41.2 months. Epiphora and discharge were the commonest presenting symptoms noted in 77.2% (17/22). Associated lacrimal anomalies include punctal agenesis, incomplete punctal canalization and atonic lacrimal sac. All patients underwent irrigation and probing under nasal endoscopic guidance. Further, 3 patients underwent endoscopic dacryocystorhinostomy for persistent CNLDO. At a mean follow up of 4.9 months, the final anatomical and functional successes were noted in 90.9% and 81.8%, respectively. Conclusions: Buried probe is a variant of complex CNLDO, noted more commonly in older children. Endoscopic guidance is crucial for its diagnosis and satisfactory outcomes. Abstract : Buried probe in complex congenital nasolacrimal duct obstructions.